2003
DOI: 10.1128/aac.47.12.3774-3779.2003
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Antileishmanial Activity of a New StableLipid Suspension of AmphotericinB

Abstract: The aim of the present study was to evaluate the toxicity and the activity of a new lipid complex formulation of amphotericin B (AMB) (LC-AMB; dimyristoyl phosphatidylcholine, dimyristoyl phosphatidylglycerol, and AMB) that can be produced by a simple process. Like other lipid formulations, this new complex reduced both the hemolytic activity of AMB (the concentration causing 50% hemolysis of human erythrocytes, >100 g/ml) and its toxicity toward murine peritoneal macrophages (50% inhibitory concentration, >10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…The use of AMB is now becoming widespread in Bihar (India) and Nepal (35), and previous reservations about the use of this potentially toxic drug have been alleviated (38). Experimental studies have also shown the possibility of reducing toxicity by heat treating AMB (4,28), and several groups are developing new formulations of AMB (1,12,13,23,24,33). Thus, it has recently been suggested that AMB should replace antimonials as the drug of choice in Bihar (37).…”
mentioning
confidence: 99%
“…The use of AMB is now becoming widespread in Bihar (India) and Nepal (35), and previous reservations about the use of this potentially toxic drug have been alleviated (38). Experimental studies have also shown the possibility of reducing toxicity by heat treating AMB (4,28), and several groups are developing new formulations of AMB (1,12,13,23,24,33). Thus, it has recently been suggested that AMB should replace antimonials as the drug of choice in Bihar (37).…”
mentioning
confidence: 99%
“…Review of the literature describing use of liposomal amphotericin B for the treatment of visceral or cutaneous leishmaniasis did not reveal any cases of confusion or any neurotoxicity related to treatment. 14,18,19 Although we cannot definitively prove that our patient's neurologic symptoms were caused by his liposomal amphotericin B treatment, we have no evidence for another more likely etiology by history, exam, and screening laboratories for metabolic causes. The time course over which he experienced this issue is consistent with the description in febrile neutropenic patients above as well as animal data detailing tissue half-lives of the drug.…”
Section: Discussionmentioning
confidence: 83%
“…Over recent years, lipid complex formulations of AmpB have been proposed, 57 showing interesting in vitro activity but less efficient than AmBisome in in vivo evaluations. More recently, liposomal formulations in which cholesterol was replaced by ergosterol, which constitutes 50% molarity of total lipids (Kalsome™ 10; Lifecare Innovations Ltd., Gurugram, India), have been evaluated.…”
Section: Liposomesmentioning
confidence: 99%